(untitled) (Global Journal of Management and Business Research, 2025)
This study investigates the influence of relational social capital focusing on trust norms of cooperation reciprocity and identification on innovation performance among Micro Small and Medium Enterprises MSMEs within Nigeria s textile manufacturing sector Operating in a resource-limited environment these MSMEs face unique challenges that make relational social capital a critical asset for sustaining competitive advantage and fostering innovation Using a mixed-method approach data was obtained from 564 respondents we integrate Partial Least Squares Structural Equation Modelling PLS-SEM and fuzzy-set Qualitative Comparative Analysis fsQCA to capture both linear and configurational effects of relational social capital Results from PLS-SEM reveal that identification significantly enhances innovation performance while other elements like trust norms of cooperation and reciprocity exert varied influences Further fsQCA identifies five unique configurations of relational social capital elements contributing to high innovation performance highlighting the essential role of identification alongside specific relational dynamics